THE APPARATUS OF INDIVIDUALISATION IN THE RUSSIAN LAN- GUAGE TEXTBOOKS ОРБИТА AND РОДНИЧОК AND OTHER ELEMENTS OF THESE TEXTBOOKS SETS - Наталија Ј. Брајковић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2014)
<!-- p { margin-bottom: 0.1in; line-height: 120%; } --> This paper examines eight textbooks of the Russian language, including the components of the analyzed textbook structures. Textbook sets such as "Орбита" and "Родничок" have been used in primary schools in Montenegro and Serbia during the last twenty years. The aim of this paper is to analyze all relevant and useful segments of the textbooks in order to help establish the design of a textbook used in foreign language teaching and learning that would be more effi cient and have better quality. Our goal is to make individualization and differentiation more realistic and profi cient, to set the principles within the textbooks and to emphasize numerous research results of the individualization based on the evaluation of the textbook corpus. We also offer a set of constructive suggestions aimed both at creating proper opportunities for the use of different strategies and at achieving different levels of individualization. According to the results and the comparison of these textbooks with those that were previously used, the main conclusion is that there is an evident presence of certain elements of individualization. The paper also gives numerous relevant, useful and important suggestions which could help generate adequate circumstances for promoting various strategies and achieving different levels of individualization.